Soft computing methods for practical environment solutions : techniques and studies - Gestal Pose, Marcos, 1977-; Rivero Cebrian, Daniel , 1978- (Hershey, PA : Information Science Reference, 2010)
Includes bibliographical references (p. 270-403) and index